Dexamethasone As Prophylaxis! is it Effective in Reducing Postoperative Extubation Blues in Paediatric Age Group? A RetrospectiveReview of 331 Patients - Pramod Patra; Debasish Nayak (Indian Journal of Anaesthesia, 2008)
Use of steroids for different airway morbidities is common. This retrospective analysis was aimed at justifying the use of dexamethasone in preventing postoperative airway morbidities during extubation in paediatric age group. Recorded data of all paediatric surgeries in a particular institute was analyzed for incidences of post extubation airway problems in patients who received dexamethasone and compared with those who did not receive any steroid perioperatively. Three hundred and thirty one patients were considered out of which 226 received intravenous dex-amethasone preoperatively, and 105 did not receive any steroids peri-operatively. Out of 52 children (15.7%) who had post-extubation airway problems, only 14 (6.1%) belonged to the dexamethasone group while 38 (36.1%) be-longed to the non-dexa group. The difference noted in the incidence between the two groups was statistically signifi-cant (p< 0.05).There was no significant incidence of any systemic adverse effects while a large number of children developed severe perianal and vulval pruritus immediately after the bolus dexamethasone injection. There was no significant difference in the incidence of subglottic or supraglottic airway morbidities when compared between both the groups. In conclusion, a single bolus preoperative intravenous dose of dexamethasone, in paediatric patients, is of immense help in reducing the airway morbidities faced at the time of extubation in the post operative period.